The growth and development of the beef qualities of Angoni cattle (East African zebu). Part I. Live weight - Walker, C.A. (Cambridge University Press, 1964)
Beef production is entirely dependent upon growth and development of an animal as influenced by both genetic and environmental factors. The growth characteristics of the Angoni, a race of the East African thoracic-humped zebu was investigated, as part of a wider scheme designed to develop the potential of the indigenous cattle of northern Rhodesia (Zimbabwe). There were smaller differences in birth weight between sexes. Birth and weaning weights were closely correlated. The live weight growth of the Angoni showed a good example of genetic balance with the highly fluctuating nutrition of the natural environment, and its growth pattern appeared largely to be controlled by the sex hormones as a race survival mechanism.